A hybrid comprehensive performance evaluation approach of cutter holder for tunnel boring machine. (April 2022) - Yang, Mei; Ji, Zhiyong; Zhang, Ling; Zhang, Aiwu; Xia, Yimin
Abstract: Cutter holder is a crucial component of tunnel boring machine (TBM), whose performance evaluation and selection needs to consider many factors, which is a challenging Multiple criteria decision-making (MCDM) problem. To enhance the TBM overall construction manifestation, it is fundamental to synthetically evaluate and accurately select the most suitable cutter holder from alternatives according to the engineering requirements and geological conditions. This paper develops a hybrid fuzzy comprehensive evaluation approach for cutter holder. In this approach, the weights of criteria are determined by Fuzzy Analytic Hierarchy Process (FAHP), and the max-min linear normalization is employed to integrate the information of qualitative and quantitative indicators of alternatives. Finally, the ranking and further comparison are achieved in the form of radar chart. A case study of cutter holder selection from six alternatives is carried out to validate the proposed approach. It shows that the proposed approach is effective, reasonable, complete and easy to operate, which can be promoted to the evaluation and selection of non-standard crucial components for large mechanical engineering equipment.